Clinical, haematological and antioxidant status in naturally poxvirus infected sheep - Issi, M.; Gul, Y.; Yilmaz, S. (Ecole Nationale Veterinaire Toulouse, 2008)
The aim of the present study was to investigate clinical and haematological findings, and antioxidant status (beta-carotene, vitamins A, E, C, reduced glutathione (GSH) concentrations vs. plasma malondialdehyde (MDA) concentrations and blood catalase activity) in sheep with spontaneous pox disease stemming from an infected herd (morbidity: 18%). In this study, blood samples were collected from 20 sick sheep, clinically diagnosed for poxvirus infection (test group) and 20 healthy sheep (control group) after clinical examination. Haematological parameters were determined using a blood cell counter whereas plasma or serum vitamin A, E, C, beta-carotene, MDA and GSH concentrations as well as catalase activity were measured spectrophometry. The diseased sheep exhibited significantly elevated body temperature, heart and breathing rates whereas rumen movements were markedly reduced compared to healthy controls. In parallel, haemoglobinemia and haemoglobin load in erythrocyte (MCHC) were also significantly decreased but the most severe alteration concerned thrombocytes whose counts were dramatically depressed. Marked increases of plasma MDA concentrations and catalase activities associated to significant reductions of concentrations of some antioxidants (glutathione, vitamin E and Q revealed the occurrence of an oxidative stress and membrane lipid peroxidation in sick animals. These results suggest that the poxvirus infection induced an exacerbated free radical formation and consumption of the principal antioxidant systems.
Keywords: pox virus; antioxidant vitamins; glutathione; free radicals; clinical and haematological parameters